Rediscovering women philosophers : philosophical genre and the boundaries of philosophy - Gardner, Catherine Villanueva (London : Routledge, 2019)
This book offers interpretations of the work of specific moral philosophers that can be used to present a challenge to what the author have been calling the view of moral philosophy. It focuses on interpreting women moral philosophers and discusses whether women have "prudence" or "natural sense."
Catharine Macaulay's Letters on education : what constitutes a philosophical system -- Allegory and moral philosophy in Christine de Pisan's The book of the city of ladies -- Mary Wollstonecraft and the separation of poetry and politics -- George Eliot and how to read novels as philosophy -- Knowing and speaking of divine love : Mechthild of Magdeburg.
Online resource; title from PDF title page (viewed July 2, 2019)
Catherine Villanueva Gardner
eBooks on EBSCOhost
Keywords: Women philosophers; Femmes philosophes; philosophers; PHILOSOPHY -- General; Women philosophers; Philosophin; Biografie; Filosofie; Vrouwen